2017
DOI: 10.4102/sajhrm.v15i0.923
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership as a mediator in the relationship between satisfaction with remuneration and the retention of artisans in the military

Abstract: Orientation: The field of leadership has been extensively researched over the last couple of decades, with a particular emphasis on the different types of leadership styles. The most valuable resource that any manager works with is human resources. Studies have indicated that the way in which people are managed is influenced by the leadership styles of managers. This, in turn, influences employee behavioural intention, including intention to quit. Retention is, in turn, influenced by a number of factors, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…In agreement with the present study, Shabane, Schultz and Van Hoek (2017) revealed that transformational leadership played a mediating role in the relationship between satisfaction with remuneration and intention to stay. It is the contention by Coomber and Barriball (2006) that satisfaction with remuneration and intention to stay are factors that play a positive role in enhancing the retention employees in organisations.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the present study, Shabane, Schultz and Van Hoek (2017) revealed that transformational leadership played a mediating role in the relationship between satisfaction with remuneration and intention to stay. It is the contention by Coomber and Barriball (2006) that satisfaction with remuneration and intention to stay are factors that play a positive role in enhancing the retention employees in organisations.…”
Section: Discussionsupporting
confidence: 93%
“…This shows that the better the transformational leadership that was applied by the leader, the better and fairer the compensation system in UNP would be. The findings of this study are in line with [11], [14], [15], [29] that state transformational leadership has a significant and positive effect on compensation.…”
Section: Discussionsupporting
confidence: 88%
“…Over the last few years, a number of studies related to job satisfaction, transformational leadership, career development, and compensation have been partially carried out and these studies have been conducted in many countries [3], [10], [15], [19], [28], [29]. They provide a theoretical basis for analyzing the effects of job satisfaction on transformational leadership, compensation, and career development.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Furthermore, transformational leadership has partially positive relationship as mediator toward the relationship of culture intelligence and voice behaviors among employees. Shabane et al (2017) conducted an observation towards 257 artisans in military unit and the findings indicated that the majority of participants, regardless of gender or ethnicity, were dissatisfied with their compensation. Transformational leadership was discovered to mediate the association between job satisfaction and intention to stay.…”
Section: Transformational Leadershipmentioning
confidence: 99%